An essay on the causes and cure of the usual diseases in voyages to the West-Indies : together with the preservatives against them [...]TT - - Monchy, Salomon de (1716-1794) (T. Becket and P. A. De Hondt, 1762)
"Document inclus dans un recueil. La page de titre du recueil porte "An inquiry into the nature, cause and cure of the croup"."